COMPARISON OF THE EFFECTIVENESS OF THE NATIONAL AMIL ZAKAT AGENCY (BAZNAS) AND DAARUT TAUHID CARE IN IMPROVING THE MUSTAHIK ECONOMY IN LAMPUNG PROVINCE - Setyorini, Tri; Noviarita, Heni; Hanif, Hanif (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The poverty experienced by the mustahik of zakat institutions in Lampung Province involves various factors and challenges that influence their economic conditions. One of the main indicators of effectiveness is the ability of zakat institutions to distribute zakat to mustahik who really need it. The aim of the research is to determine the comparative effectiveness of the National Zakat Amil Agency (BAZNAS) and Daarut Tauhid Peduli in developing the mustahik economy in Lampung Province. The method used is qualitative with a field research approach and descriptive analysis. The research was conducted at Lampung Province Amil Zakat Institutions, namely the National Zakat Agency (BAZNAS) Lampung Province and Daarut Tauhid Peduli Lampung Province. The results of the research show that the implementation of the zakat amil institutions (BAZNA and DT Peduli) program is by distributing funds to mustahik in the form of providing business capital and assistance with production equipment, apart from that in the form of assistance to farmers and breeders, as well as assistance in developing Small and Medium Enterprises ( SMEs). The economic condition of the mustahik before receiving assistance from the amil zakat institution was very difficult in meeting economic needs and was hampered in developing the business they were running. engaged in. The effectiveness of the role of zakat amil institutions in improving the Mushik economy has made a real contribution.